2008
DOI: 10.1104/pp.107.113613
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Manganese Superoxide Dismutase Leads to Reduced Root Growth and Affects Tricarboxylic Acid Cycle Flux and Mitochondrial Redox Homeostasis    

Abstract: Superoxide dismutases (SODs) are key components of the plant antioxidant defense system. While plastidic and cytosolic isoforms have been extensively studied, the importance of mitochondrial SOD at a cellular and whole-plant level has not been established. To address this, transgenic Arabidopsis (Arabidopsis thaliana) plants were generated in which expression of AtMSD1, encoding the mitochondrial manganese (Mn)SOD, was suppressed by antisense. The strongest antisense line showed retarded root growth even under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
117
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(126 citation statements)
references
References 71 publications
9
117
0
Order By: Relevance
“…Since then researchers have taken advantage of this tool to monitor the redox state involved in glutathione metabolism (Meyer et al, 2007) or the removal of ROS by manganese superoxide dismutase in mitochondria (Morgan et al, 2008), and additional papers are anticipated. Other valuable methods for in vivo monitoring of ROS were also introduced, including autoluminescence (Havaux et al, 2006) and biophotone imaging (Kobayashi et al, 2007) as well as luciferase imaging (Shao et al, 2007).…”
Section: Advances In Ros Imagingmentioning
confidence: 99%
“…Since then researchers have taken advantage of this tool to monitor the redox state involved in glutathione metabolism (Meyer et al, 2007) or the removal of ROS by manganese superoxide dismutase in mitochondria (Morgan et al, 2008), and additional papers are anticipated. Other valuable methods for in vivo monitoring of ROS were also introduced, including autoluminescence (Havaux et al, 2006) and biophotone imaging (Kobayashi et al, 2007) as well as luciferase imaging (Shao et al, 2007).…”
Section: Advances In Ros Imagingmentioning
confidence: 99%
“…For mitochondria isolation, Arabidopsis (Arabidopsis thaliana; ecotype Columbia [Col-0]) seedlings were grown in liquid culture as described in Morgan et al (2008). For growth on plates, Arabidopsis seeds were treated and grown the same way except that the medium was supplemented with 0.8% (w/v) phytoagar.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Mitochondria were isolated from 10-d-old Arabidopsis seedlings grown in liquid cultures as described before (Morgan et al, 2008). The integrity of the outer membrane was determined by the latency of cytochrome c oxidation before and after addition of Triton-X100 (Sweetlove et al, 2007).…”
Section: Isolation Of Organellesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsp70 was involved in instrumenting root-shoot communication in cucumber plants (Li et al 2014) whereas expression of hsp81-2 was found high in roots of Arabidopsis thaliana (Yabe et al 1994). In addition, a gene encoding for superoxide dismutase (SOD) is major component of plant defence system but decrease in manganese superoxide dismutase leads to reduced root growth (Morgan et al 2008). Other identified genes like glutathione peroxidase, cinnamic acid 4-hydroxylase and ACC oxidase have been involved in root metabolism and growth (Passaia et al 2013;Dennis and Kennedy 1986).…”
Section: Discussionmentioning
confidence: 99%